Housing and choice in Iquique and Alto Hospicio, Chile: Possibilities and limitations regarding the 2030 agenda and SDG 11 - Alvarado Peterson, Voltaire; Rojo-Mendoza, Félix (Frontiers in Communication, 2023)
Access to housing, more than an enforceable right, has become a multidimensional problem in Chile. Faced with the impossibility of obtaining housing through subsidies, informal settlements – camps and land grabs – have expanded through the country’s different cities since 2019. Given the evident collision with the SDG 11 commitments to sustainable cities, the Chilean State has increased its housing budget since 2020 to reactivate investment during the COVID 19 pandemic and expand the housing access alternatives for lower-class families with few possibilities chances of obtaining a bank mortgage. But is it possible to choose housing in contexts like the one described? In addition to environmental difficulties, cities in northern Chile, wedged between the sea and the desert, need to produce a socially sustainable environment in accordance with the requirements of complex, dynamic systems under permanent pressure to generate well-being. This manuscript seeks to explore and analyze these tensions in the cities of Iquique and Alto Hospicio, in Chile’s Tarapacá Region. They form a dynamic conurbation, where daily mobility and the dispute over access to housing clash with the choice offered by the different subsidy programs and the expansion of camps on the edges of the desert. So, how far or how close is SDG 11 in places like these? Is there a viable alternative for urban sustainability in precarious spaces?